Analisis Pengelolaan Keuangan Dana Bantuan Operasional Sekolah (BOS) Pada Madrasah Tsanawiyah Darul Falah Aek Songsongan Kabupaten Asahan - Yuli Nur’aini; Nurlaila Nurlaila; Khairina Tambunan (Universitas Labuhanbatu, 2023)
This study aims to determine the planning and preparation in managing school operational assistance funds (BOS), the realization of the school operational assistance fund (BOS) budget that has been planned, and to find out the supporting and inhibiting factors in managing school finances at MTs Darul Falah Aek Songsongan, Asahan Regency. This study used a qualitative research method with a descriptive approach. The data collection techniques used were observation, interviews and documentation. The results showed that the planning and preparation of the school operational assistance fund (BOS) budget carried out by MTs Darul Falah Aek Songsongan was effective and efficient referring to the planning that had been designed in the RAPBS and was in accordance with BOS technical guidelines. The realization of the management of school operational assistance funds (BOS) at the MTs Darul Falah Aek Songsongan school has been carried out effectively and efficiently and is also based on the principles referred to in the Government Regulation of the Republic of Indonesia Number 48 of 2008. Factors supporting the existence of collaboration involving several school stakeholders between committees, foundations, treasurers, madrasah heads and several teachers who are transparent (open). Meanwhile, the inhibiting factors stemming from delays in the disbursement of school operational assistance funds (BOS) and the allocation of adjusted funds are still insufficient because the budget obtained is not in proportion to the needs of the school.